DEVELOPMENT AND FEASIBILITY EVALUATION OF AN ANDROID-BASED ELECTRONIC MODULE FOR MATHEMATICS LEARNING IN JUNIOR SECONDARY EDUCATION - Abdul Haris Indrakusuma; Vertika Panggayuh; Fahrur Rozi; Richo Prastianto (STKIP PGRI TULUNGAGUNG, 2024)
The integration of mobile technology into formal education has generated substantial interest in the development of Android-based learning media, particularly in subjects that students traditionally find challenging. This study addresses the limited availability of interactive, portable learning tools for eighth-grade mathematics specifically on the topic of three-dimensional flat-sided geometric solids at SMP Negeri 6 Tulungagung, where mathematics consistently recorded the lowest average scores among twelve subjects. The primary objective was to develop and evaluate the feasibility of an Android-based electronic module (e-module) built with Construct 2, following the four-stage 4D (Define, Design, Develop, Disseminate) research and development model. The e-module was systematically validated through two media experts, one content expert, and field-tested with 74 students across small-group and large-group trials. Validation and user-response data were collected via structured questionnaires and scored against a five-tier eligibility rubric. Results indicate that media expert validation yielded scores of 84% and 99%, respectively; content expert validation returned 90.9%; and student user trials recorded 92% and 94.5% for small and large groups, respectively. The overall mean feasibility score was 92.1%, falling within the Very Eligible category. These findings confirm that the developed e-module meets the pedagogical, technical, and usability standards required for deployment in classroom and independent learning contexts. The study contributes a replicable development framework for mobile-based mathematics learning media in resource-constrained secondary school environments and highlights directions for future work, including cross-platform deployment and integration of adaptive assessment features.